MONITORING SYSTEM FOR BUILDING DEFORMATION DURING CONSTRUCTION IN URBAN DEVELOPMENT - Олейник, В.А.; Безушко, Денис; Корлюга, А.А. (SWorldJournal, 2022)
A variant of the system for monitoring the technical condition during the construction of an object in a dense urban area is presented. The work uses modern design methods implemented in the Autodesk AutoCad and Revit software systems, stress-strain state